2009
DOI: 10.1182/blood-2008-02-140038
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of resistance to 5-aza-2′-deoxycytidine in human cancer cell lines

Abstract: 5-aza-2-deoxycytidine (DAC) is approved for the treatment of myelodysplastic syndromes, but resistance to this agent is common. In search for mechanisms of resistance, we measured the half maximal (50%) inhibitory concentration (IC 50 ) of DAC and found it differed 1000-fold among a panel of cancer cell lines. The IC 50 was correlated with the doses of DAC that induced the most hypomethylation of long interspersed nuclear elements (LINE; R ‫؍‬ 0.94, P < .001), but not with LINE methylation or DNA methyltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
187
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 212 publications
(202 citation statements)
references
References 34 publications
9
187
0
2
Order By: Relevance
“…This was confirmed by the selection and characterization of decitabine-resistant rat leukemic cell lines that revealed mutations in the dCyd kinase gene (Stegmann et al, 1995). Similar results were obtained in more recent studies with human cancer cells, where decitabine sensitivity could be restored by transfection of the wild-type dCyd kinase (Qin et al, 2009). dCyd kinase has also been used to predict in vivo sensitivity and resistance to other cytidine analogs, such as gemcitabine and cytarabine, in patients (Flasshove et al, 1994;Kroep et al, 2002).…”
Section: Metabolic Activation and Cellular Transport Of Dnmt Inhibitorssupporting
confidence: 83%
See 1 more Smart Citation
“…This was confirmed by the selection and characterization of decitabine-resistant rat leukemic cell lines that revealed mutations in the dCyd kinase gene (Stegmann et al, 1995). Similar results were obtained in more recent studies with human cancer cells, where decitabine sensitivity could be restored by transfection of the wild-type dCyd kinase (Qin et al, 2009). dCyd kinase has also been used to predict in vivo sensitivity and resistance to other cytidine analogs, such as gemcitabine and cytarabine, in patients (Flasshove et al, 1994;Kroep et al, 2002).…”
Section: Metabolic Activation and Cellular Transport Of Dnmt Inhibitorssupporting
confidence: 83%
“…Gene expression analyses that demonstrated a positive correlation between hENT1 expression and 5-azacytidine potency in human cancer cell lines provided a first indication for an important role of hENTs in 5-azacytidine uptake (Huang et al, 2004). Furthermore, low expression levels of hENT1 and hENT2 were detected in cells resistant to decitabine (Qin et al, 2009). As hENT transporters show ubiquitous expression, they can have a major role in the sensitivity and resistance of cancer cells to azanucleoside DNMT inhibitors.…”
Section: Metabolic Activation and Cellular Transport Of Dnmt Inhibitorsmentioning
confidence: 99%
“…2014), and loss of DCK function was also reported in decitabine‐resistant cells (Qin et al. 2009). To characterize the mechanisms of azacitidine resistance, protein expression of UCK2, one of the enzymes to activate azacitidine, and DCK, an enzyme to activate decitabine, was measured in four cell lines.…”
Section: Resultsmentioning
confidence: 99%
“…Loss of DCK function is reported to be one of the mechanisms of decitabine resistance (Qin et al. 2009, 2011). Unexpectedly, the expression levels of DCK in the azacitidine‐resistant cells in the present study were not changed, although those azacitidine‐resistant cells showed strong cross‐resistance to decitabine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation